(untitled) (The Journal of Psychology and Sociology, 2015)
This research paper aims to study the relationship between the personality characteristics and the attitude to the unconscious manifestations of terrorism in the age aspect. One of the most actual problems on a global scale is ter rorism – an issue that concerned the entire world community. This study set such tasks as, firstly, the implementation of the selection methods of psycho diagnostics, adequate for the study of the topic, and secondly, secondly, after an interpreting the results of the application of research methods to identify common trends in the relationship between personal characteristics, depend ing on age. Third, to identify further ways of current research related to the perception of terrorism. Review of the problem in the age aspect involves the study respondents of early, middle and late adulthood. The course of study is characterized by the use of such techniques of psychodiagnostics as author quastionnaire, testing «incomplete sentences» by the method of SachsLevi, the ranking of primary colors by the method of M. Lusher, with a further ap plication of the method «Color Test relations», developed by A. M. Etkind.